Impact Assessment of Presidential Regulation No. 17 of 2019 on Assets of Indigenous Papuan Entrepreneurs in Mimika Regency - Ida Lamtiur Sianturi; Elsyan R. Marlissa (Goodwood Publishing, 2026)
Purpose: This study aims to evaluate the impact of Presidential Regulation No. 17 of 2019 on the assets of Indigenous Papuan (OAP) entrepreneurs in Mimika Regency, focusing on sustainability, participation, and challenges in procurement activities. Research methodology: A qualitative descriptive approach was applied using interviews, questionnaires, and documentation. Data analysis followed the Miles and Huberman method, including data reduction, display, and conclusion drawing. Results: Findings reveal that 71% of OAP entrepreneurs operate in construction, while 19% are engaged in goods and 10% in services. Most businesses have been operating for 4–6 years (33%). Despite high awareness of the regulation (81%), participation in procurement remains low, with 48% of respondents involved only sporadically. Key constraints include limited business capital (38%), lack of information (19%), and intense competition (19%). In terms of assets, cash capital dominates (71%), followed by business premises (52%), equipment (48%), and operational vehicles (43%). Procurement participation has positively influenced business assets, with 67% reporting increased capital and equipment, though 24% saw no significant improvement. Conclusions: The regulation has had a positive effect on asset growth and business development of OAP entrepreneurs, yet implementation remains uneven. Enhanced information access, transparency in procurement, and stronger support in capital and training are needed for greater impact. Limitations: The study is geographically limited to Mimika Regency and relies on descriptive qualitative data, which may restrict broader generalization. Contribution: The research contributes empirical evidence on the link between national policy implementation and indigenous entrepreneurship development in Papua.